Technical Note: On the use of the mushy-layer Rayleigh number for the interpretation of sea-ice-core data - Vancoppenolle, Martin; Notz, D; Viviers, F; Tison, Jean-Louis; Delille, Bruno; Carnat, Gauthier; Zhou, Jiayun; Jardon, F.; Griewank, P.; Lourenço, A. (2013)
info:eu-repo/semantics/published